Jihad Ekologi dalam Islam: GreenFaith Indonesia dan Eco Bhinneka Muhammadiyah - Parlan, Hening Purwati (MAARIF, 2024)
Ecological jihad is a paradigm that integrates religious teachings as inspiration to raise awareness and encourage collective action in environmental conservation. This article examines the role of religion in motivating the ecological movement by highlighting the experiences of interfaith communities in Indonesia, such as Eco Bhinneka Muhammadiyah and GreenFaith Indonesia. Based on empirical data and environmental theories such as eco-justice and eco-theology, ecological jihad emphasizes the importance of integrating spiritual values, environmental ethics, and social justice in facing global challenges such as climate change, biodiversity destruction, and pollution. This article also highlights the relevance of ecological jihad in addressing social inequality exacerbated by the environmental crisis, while providing faith-based solutions oriented towards sustainability. This approach is realized through education, community action, and policy advocacy as a sustainable transformation movement.